The Influence of Perceived Ease of Use on Online Purchasing Decisions on E-Commerce Shopee in Solokanjeruk District, Bandung Regency - Fadillah, Sugiharto; Septiani, Nisa; Janah, Nisa Raudatul (Universitas Indonesia Membangun (Inaba), 2024)
The Shopee E-Commerce application is an online buying and selling site and is one of the e-commerce sites currently developing in Indonesia, including in the Solokanjeruk District area. Even though online shopping has numerous benefits, the complexity of using the website itself, in this case an online shopping site, can be something that can confuse users. So, this research aims to determine the influence of Perceived Ease of Use on online purchasing decisions at Shopee E-Commerce in Solokanjeruk District, Bandung Regency. Knowing the ease of use of Shopee will increase sales at the Shopee marketplace. The method used in this research is quantitative using associative descriptive research. With a population of Shopee application users in Solokanjeruk District of 16,254 people. The sampling technique used was probability sampling with simple random sampling and using the Slovin formula to obtain a sample of 100 respondents. The research results show that Perceived Ease of Use has a significant influence on online purchasing decisions at Shopee E-Commerce in Solokanjeruk District, Bandung Regency. From these results it can be concluded that the null hypothesis is rejected, and the alternative hypothesis is accepted so that